Didactic proposal for virtual learning environments from the praxeological approach - Saza, Ilber Darío (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The virtual learning environments have transformed education, which has generated changes in teaching methods, learning modalities and styles, among other aspects. The versatility and the wide range of options offered by digital technologies allow finding different academic and professional training applications. However, new questions have been raised about how to create a virtual learning environment such as: what is the starting point? How to teach? How to assess? The present text focuses on one of the specific objectives of the research project Impact of the instructional design in teaching and learning processes, which describes the experiences of engineering teachers regarding virtual classrooms and the convergence with the praxeological approach, pedagogical approach of Uniminuto. Data were obtained by direct observation and interviews. This process was complemented by surveys. The present research uses mixed methods and seeks to explain the impact of teacher training in the process of creating virtual learning environments.